Social Interactions of Gifted Children in Heterogeneous Environment - Donii E.I. (Психолого-педагогические исследования, 2018)
The article studies the social interaction of gifted children with their peers. Understanding the educational environment and the nature of social interaction helps developing necessary interventions with the goal to make a gifted child adapted. The goal of the paper is the analysis of the foreign literature; representation of the results of empirical research of social status and social interaction of gifted children in elementary school hold in 2016 in Holland. The used instruments: sociometric questionnaire of Rodriguea and Morera; behavior analysis protocol OPINTEC-v.5. Out of eight participants, one was the most rejected among peers (5th grade), two became the most popular among peers (3rd grade). The gifted children chose gifted and non-gifted children for interaction and established close interactions with them. When working together, the gifted children interacted more with popular and neutral peers; when playing together — with neutral peers. With reference to social interaction of gifted children with peers, only patterns demonstrating social effectiveness and social correspondence were found out.